2003
DOI: 10.1037/0022-006x.71.4.805
|View full text |Cite
|
Sign up to set email alerts
|

Social support as a mediator of optimism and distress in breast cancer survivors.

Abstract: Breast cancer patients can experience emotional distress as a result of diagnosis and treatment. Higher levels of optimism and social support are associated with less emotional distress in cancer patients. This 12-month prospective study followed 69 women who had completed treatment for Stages 0-II breast cancer. At 3-month intervals, participants completed measures of mood disturbance, optimism, and social support. As hypothesized, affective social support mediated the relationship between optimism and distre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
91
2
6

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(111 citation statements)
references
References 57 publications
10
91
2
6
Order By: Relevance
“…For this reason, we created an index of mood disturbance (cf. Trunzo & Pinto, 2003) by averaging the 10 items (␣ ϭ .87). The mean distress rating was 1.76 (SD ϭ 0.70), indicating a mild level of negative affect.…”
Section: Adjustment Measuresmentioning
confidence: 99%
“…For this reason, we created an index of mood disturbance (cf. Trunzo & Pinto, 2003) by averaging the 10 items (␣ ϭ .87). The mean distress rating was 1.76 (SD ϭ 0.70), indicating a mild level of negative affect.…”
Section: Adjustment Measuresmentioning
confidence: 99%
“…It has been theorized that optimists are more socially attractive than pessimists, and consequently they are more likely to be integrated into supportive social networks, and to receive favorable responses from their social environment (e.g., Scheier & Carver, 1987). Various studies have shown a positive relationship between optimism and perceived available social support, such as the availability of helpful others (e.g., Brissette, Scheier, & Carver, 2002;Fontaine & Seal, 1997;Trunzo & Pinto, 2003), and received social support, such as the frequency of helpful interactions (Aspinwall & Taylor, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…A fenti értelmezési kereteken túl fontosnak tartjuk itt is megemlíteni, hogy az optimista attitûd pozitív összefüggést mutat több egészségmuta-tóval, és a betegséggel való megküzdés sikerességével (Bozo és mtsai, 2009;Carver és mtsai, 1993Carver és mtsai, , 2005Dunn és mtsai, 2011;Matthews & Cook, 2009;Schou és mtsai, 2005a;Trunzo & Pinto, 2003). Tehát ha az optimizmus "oká-ra" csak feltevéseink is lehetnek, lényegében örömteli eredmény az, hogy a mintákban vizsgált daganatos betegek az elmúlt évben tapasztalt rossz lelkiállapotuk ellenére egy aktív, pozitív megküzdési stratégiát alkalmaznak a betegséggel való megküzdési/gyógyulási folyamatuk során.…”
Section: A Keresztmetszeti Adatok éRtelmezéseunclassified
“…A túlélés-, optimizmus-és betegségstádium-változók együttes vizsgálata és elemzése sem hozott szignifikáns különbséget az egyes csoportok között, tehát a prognosztikai szempontok sem mutattak összefüggést az optimizmussal és túléléssel. Ezek az eredmények ellentmondani látszanak a szakirodalomban az optimizmus gyógyulással és sikeres megküzdéssel való együttjárásáról szóló eredményeknek (Carver és mtsai, 2005;Giese-Davis & Spiegel, 2003;Trunzo & Pinto, 2003).…”
Section: Az Utánkövetés Eredményeinek éRtelmezéseunclassified